Antibacterial Cinnamon Essential Oil Incorporated Poly(Ɛ−Caprolactone) Nanofibrous Mats: New Platform for Biomedical Application - Phaiju, Surakshya; Mulmi, Purnima; Shahi, Dikpal Kumar; Hwang, Tae In; Tiwari, Arjun Prasad; Joshi, Rajendra; Pant, Hem Raj; Joshi, Mahesh Kumar (Journal of Institute of Science and Technology, 2020)
Wound healing is a complex process and prevention of wound infection is crucial for wound care as colonization of bacteria delays the healing process. For rapid healing, the wound dressing should have an antibacterial property and biocompatible. Herein, we proposed the use of cinnamon essential oil, a natural antimicrobial agents, incorporated electrospun poly(ɛ-caprolactone) (PCL) fibrous dressings. The wound dressing scaffolds were successfully prepared by electrospinning of the blend solution of poly(ɛ-caprolactone (PCL) with different concentrations of cinnamon essential oil. The mats were characterized by field emission scanning electron microscopy (FESEM), Fourier transform infra-red (FTIR), thermal gravimetric analysis (TGA), and differential scanning calorimetry (DSC) analysis. FESEM results revealed that the incorporation of cinnamon oil generated the membrane with fine fibers along with nanofibers compared to uniformly distribute the nanofibers for pristine PCL. Experimental results of cell viability assay and microscopy imaging showed that the as-fabricated composite wound dressing scaffold exhibited excellent cell viability for fibroblast (NIH-3T3) cells. The antimicrobial activity of the composite scaffold was assessed from the zone of inhibition against Gram-positive and Gram-negative bacteria. Results indicated that the fibrous mats inhibited the growth of Gram-positive bacteria Staphylococcus aureus and Gram-negative bacteria- Escherichia coli, Salmonella typhimurium, and Pseudomonas aeruginosa showing high antibacterial activity. Overall, our results concluded that the introduced scaffold might be an ideal biomaterial for wound dressing applications.